2016
DOI: 10.1186/s12883-016-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

Case control study: magnetic resonance spectroscopy of brain in HIV infected patients

Abstract: BackgroundIn vivo proton magnetic resonance spectroscopy (1H-MRS) studies on brain in HIV infected patients have shown significant alteration in neuro-biochemicals.MethodsIn this study, we measured the neuro-biochemical metabolites from the left frontal white matter (FWM) and left basal ganglia (BG) caudate head nucleus in 71 subjects that include 30 healthy controls, 20 asymptomatic HIV and 21 HIV patients with CNS lesion. Proton MR spectra were acquired at 3 T MRI system and the concentration (institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…When comparing HIV-positive patients of different age groups with age-matched healthy subjects, the results of our study showed that NAA/Cr ratios were significantly decreased in chronically infected, virally suppressed HIV-positive subjects, compared to healthy controls. This has also been observed in previous spectrosopic studies ( Bairwa et al, 2016 ; Boban et al, 2017 ). In HIV-positive subjects, the presence of HIV infection was the strongest contributor to this decline, followed by age.…”
Section: Discussionsupporting
confidence: 90%
“…When comparing HIV-positive patients of different age groups with age-matched healthy subjects, the results of our study showed that NAA/Cr ratios were significantly decreased in chronically infected, virally suppressed HIV-positive subjects, compared to healthy controls. This has also been observed in previous spectrosopic studies ( Bairwa et al, 2016 ; Boban et al, 2017 ). In HIV-positive subjects, the presence of HIV infection was the strongest contributor to this decline, followed by age.…”
Section: Discussionsupporting
confidence: 90%
“…However, Cr expression is variable with age, trauma, and inflammation. Other key metabolites in the brain are glutamate and glutamine that has been associated with cognitive disease in the HIV-infected population [66] . The combination of these metabolites has become extremely important due to the fact that glutamate and Cr are highly abundant in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to appearing to lack a sufficiently reproducible effect size for application to rule-based diagnostics of single individuals, reductions in N-acetyl aspartate in normal-appearing or lesioned brain matter are also not specific to multiple sclerosis, also having been found in diabetes mellitus cortex (298), lupus gray and white matter (299), and HIV basal ganglia (300). Moreover, among conditions demonstrating lesion activity on magnetic resonance imaging for which 1 H-MRS might serve as an auxiliary toward differential diagnosis, N-acetyl aspartate has similarly been reported to decrease in, among others, acute disseminated encephalomyelitis lesions (301) and lesioned tissue in patients with cerebral small vessel disease (SVD) (302).…”
Section: Outlook and Conclusionmentioning
confidence: 99%